Enhanced high-throughput embryonic photomotor response assays in zebrafish using a multi-camera array microscope - Julia Jamison; Thomas Jedidiah Jenks Doman; Zoe Antenucci; John Efromson; Connor Johnson; Michael T. Simonich; Mark Harfouche; Lisa Truong; Robyn L. Tanguay (SLAS Technology)
Developing automated, high-throughput screening platforms for early-stage drug development and toxicology assessment requires robust model systems that can predict human responses. Zebrafish embryos have emerged as an ideal vertebrate model for this purpose due to their rapid development, genetic homology to humans, and amenability to high-throughput screening. However, existing commercial imaging platforms face significant technical limitations in capturing early developmental behaviors. We present the validation of the Kestrel™, a novel high-throughput imaging platform featuring a 24-camera array that enables simultaneous acquisition of high-resolution video data across 96-well plates. This system overcomes key technical limitations through its unique optical design and automated image processing pipeline. Unlike current commercial systems, which require specialized setup and can only image subsets of wells, the Kestrel provides comprehensive plate imaging at 9.6 µm resolution with 10+ Hz video capture across an 8 × 12 cm field of view. We validated the system using zebrafish embryonic photomotor response (EPR) assays, demonstrating its ability to track behavioral responses in chorionated and dechorionated embryos without workflow modifications. The system successfully detected concentration-dependent responses to ethanol, methanol, and bisphenol A across different plate formats and well volumes. Notably, the Kestrel enabled equivalent detection of behavioral responses in chorionated and dechorionated embryos, eliminating the need for the dechorionation process while maintaining assay sensitivity. This technological advancement provides a robust platform for high-throughput chemical screening in drug discovery and toxicology applications, offering significant improvements in throughput, sensitivity, and reproducibility with a highly relevant vertebrate model.